Chlamydia Pneumoniae Pneumonia: An Evolving Clinical Spectrum - David Megran; Rosanna W Peeling; Thomas J Marrie (Canadian Journal of Infectious Diseases)
Chlamydia pneumoniae is a recently recognized respiratory tract pathogen. It accounts for 6 to 10% of all cases of community acquired pneumonia requiring admission to hospital. Two patients hospitalized with C pneumoniae pneumonia are presented to illustrate its range of severity and the extrapulmonary manifestations.